2007
DOI: 10.4028/www.scientific.net/msf.539-543.2269
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Deformation and High Velocity Impact Behaviors of Ti-6Al-4V Alloys

Abstract: Deformation behaviors under quasi-static and dynamic compression and high velocity impact condition of Ti-6Al-4V ELI (extra low interstitial) alloys in two different conditions were investigated. Mill annealed (MA) alloy, consisted of equiaxed α, and thermomechanically treated (TMT) alloy, consisted of mixed structure of equiaxed α and transformed β, were prepared. Compression tests were performed in low strain rate regime using hydraulic testing machine and were performed in high strain rate regime using spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This decrease in the additional eigenstrain introduced with each successive layer is due to the pre-existing residual stress state, which acts to inhibit further yield of the material. With a work-hardening material this effect will be even marked, although it should be noted that Ti-6Al-4V shows very low levels of work hardening [14] and the material model assumed here is probably appropriate.…”
mentioning
confidence: 93%
“…This decrease in the additional eigenstrain introduced with each successive layer is due to the pre-existing residual stress state, which acts to inhibit further yield of the material. With a work-hardening material this effect will be even marked, although it should be noted that Ti-6Al-4V shows very low levels of work hardening [14] and the material model assumed here is probably appropriate.…”
mentioning
confidence: 93%
“…Titanium alloy Ti–6Al–4V was chosen in the present study because of its use in compressor blades of aircraft engines. Typically, the level of work hardening in the material is not marked, 6 and an elastic/perfectly plastic behaviour (yield stress = 1000 MPa; Young's modulus = 110 GPa; Poisson's ratio = 0.3; and density = 4400 kg/m 3 ) was assumed in the current analyses; this is satisfactory for the purpose of validating the approach. 13 The results of earlier analyses 12 show that during LSP, material will be subject to high strain rates (∼10 6 s −1 ).…”
Section: Analysis Of Lsp Treatment Of a Right-angle Free Edgementioning
confidence: 99%
“…Titanium alloy Ti-6Al-4V was chosen in the present study because of its use in compressor blades of aircraft engines. Typically, the level of work hardening in the material is not marked 6 , and an elastic/perfectly-plastic behaviour (yield stress =1000 MPa;…”
Section: Explicit Finite Element Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium alloys have been investigated for their application as an armor technology, and technical papers about the possible replacement of steel with titanium alloy were published in many journals [4][5][6][7][8][9][10][11][12][13][14][15][16]. As early as 1950, the researchers found that titanium alloys have an application prospect as armors against small arms projectiles [4].…”
Section: Introductionmentioning
confidence: 99%